2015
DOI: 10.1149/2.0291512jes
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sulfur Formation on Performance and Reforming Chemistry of SOFC Anodes Operating on Methane Containing Fuel

Abstract: This paper presents a detailed analysis of the influence of sulfur formation on performance and efficiency of Solid Oxide Fuel Cells (SOFC) operating on methane containing fuels. Our previously developed multi-step reaction mechanism of sulfur formation and oxidation is coupled with a complex heterogeneous mechanism of methane reforming, channel gas-flow, porous-media transport and elementary kinetic charge transfer and is used to describe sulfur-induced degradation and performance drops of Ni/YSZ anodes. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…However,t he affected processi ss till at af requency 2-3 orders of magnitude lower than that of Ni/ YSZ, whichi sc aused by the double layer capacitance at the interface between Ni and YSZ. [2,7] Although the peak frequency of the affected process is significantly higherf or cell Bt han for cell A, the overall sulfur poisoning behaviorr emains similar both in regard to the magnitude of the performance drops and their evolution with H 2 Sconcentration and current density. Undert he assumption thatt he resistances of both anode processesa re approximately the same, the capacitance of the sulfur-affected process for the Ni/CGO40-based anode can be estimated to be twice that of Ni/CGO10.…”
Section: Sulfur Poisoning Of Ni/cgo40-based Anodesmentioning
confidence: 96%
See 2 more Smart Citations
“…However,t he affected processi ss till at af requency 2-3 orders of magnitude lower than that of Ni/ YSZ, whichi sc aused by the double layer capacitance at the interface between Ni and YSZ. [2,7] Although the peak frequency of the affected process is significantly higherf or cell Bt han for cell A, the overall sulfur poisoning behaviorr emains similar both in regard to the magnitude of the performance drops and their evolution with H 2 Sconcentration and current density. Undert he assumption thatt he resistances of both anode processesa re approximately the same, the capacitance of the sulfur-affected process for the Ni/CGO40-based anode can be estimated to be twice that of Ni/CGO10.…”
Section: Sulfur Poisoning Of Ni/cgo40-based Anodesmentioning
confidence: 96%
“…[50] However, recent studies have suggested the converse behavior. [2,5,7] Thus, the observed mitigation effect might be relatedt oi mproveda node kinetics because of increased humidity levels in the anode compartment rather than to the actual sulfur oxidation to SO 2 and its subsequentr emoval from the anode surface. Furthermore, the increase of the ASR values for the OCV experiment are lower than at an appliedc urrent density of 0.25 Acm À2 ,w hich is inconsistent with the hypothesis of SO 2 formation.N onetheless, recentD FT calculations of sulfur oxidation on doped cerias urfaces showedt hat sulfur oxidation to SO 2 displays favorable kinetics as surface lattice oxygen could be used to oxidizethe ceria-adsorbed sulfur.…”
Section: Influence Of Currentd Ensity and Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Having identified the existence of sulfur adsorbates serving to mask active sites for hydrocarbon reforming, it may now be possible to propose a better solution for mitigating the problem. First, it appears that the free surface of Ni (Ni-gas two-phase boundary, 2PB) is directly related to the sulfur uptake property. , Thus, even with a finite Ni mass load, it is expected that smaller Ni particles, possibly nanoparticles, with a higher surface area can tolerate greater levels of sulfur contaminants. Moreover, as the particle diameter d decreases, the TPB length increases proportionally to d –2 ; hence, S* will have a greater chance to be removed as SO 2 with the aid of oxygen ion flux from the adjacent electrolyte phase, i.e., This further explains the excellent sulfur tolerance reported for anodes with exsolved Ni nanoparticles. , Given that Ni is likely to be dissolved into the YSZ phase at a high temperature and can later be exsolved, employing such nanoparticles may significantly enhance the tolerance to sulfur poisoning of Ni-based anodes.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfur poisoning effect of nickel-based catalysts was first studied in the catalytic process of biomass/coal gasification , and steam reforming. , Recently, sulfur poisoning in the dry reforming process has also been investigated , because sulfur impurities are inevitably produced during the process of biogas production, and the presence of even low sulfur levels after desulfurization may lead to the deactivation of nickel catalysts. , It has been accepted for decades that catalysts can be deactivated by sulfur via the chemisorption of sulfur with active metal to form metal sulfides (eq ), which occupy the surface active sites, deactivating the catalyst. , However, the detailed sulfur poisoning performance and mechanism in a biogas dry reforming process with regard to the formation and elimination of Ni–S species still remains unclear. …”
Section: Introductionmentioning
confidence: 99%